Periodontal surgery as treatment of periodontitis stage 1 grade A: Bedah periodontal sebagai tatalaksana periodontitis stage 1 grade A - Qonitah Nur Aslamiyah; Farah Fathia Fauzia; M. Rijal Dermawan K; Steffi Triany Arnov (Makassar Dental Journal, 2026)
Periodontitis is an inflammatory disease of the periodontal tissues caused by certain microorganisms and characterised by the loss of periodontal tissue. Ac-cording to the American Academy of Periodontology in 2018. Periodontitis is classified into four stages based on the severity of the disease and the complex-ity of treatment, and three grades based on its progression. A 20-year-old woman presented to the Periodontology Department of RSGMP Unimus in Septem-ber 2024 with complaints of swollen gums and frequent bleeding during toothbrushing. Based on the medical history, clinical examination, and supporting tests, the patient was diagnosed with stage 1 grade A periodontitis accompanied by gingival enlargement. It was concluded that periodontal surgery showed a good success rate, resulting in the gingiva no longer being enlarged, having a coral pink colour, a firm consistency, stippling, and sharp interdental papillae.